Peningkatan Kebersihan Prasarana Ibadah Masyarakat Desa Sambungrejo, Kecamatan Sukodono, Kabupaten Sidoarjo Sebagai Bentuk Pengabdian Kepada Masyarakat oleh Mahasiswa Universitas Sunan Giri Surabaya - Imam Hambali; Habib Muhammad Bahaus Surur; Ikhwanuddin Ikhwanuddin; Mohammad Rasikhul Islam; Andrian Firdaus Yusuf; Sudarso Sudarso; Muhammad Yusron Maulana El-Yunusi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Environmental cleanliness is a major concern in the community of Sambungrejo Village, Sukodono District, Sidoarjo Regency. To overcome the problem of cleanliness in mosques located in residential areas, cleaning activities were carried out through community service involving participants of the Real Work Lecture (KKN) from Sunan Giri University Surabaya. The main purpose of this activity is to educate the people of Sambungrejo Sukodono Village about the importance of keeping the mosque clean, train students to have concern for the sanctity and comfort of places of worship, and carry out the principles of the Tri Dharma of Higher Education. This activity is part of the Community Service program carried out by KKN Group 11 students of Sunan Giri University Surabaya, held in Sambungrejo Village, Sukodono District, Sidoarjo Regency on August 4, 2023. During the mosque cleaning activity, KKN students involved the community service method to clean and tidy up the facilities in the mosque. The cleaning process begins with cleaning the mosque yard, followed by cleaning the men's and women's bathrooms, as well as cleaning the Al-Qur'an and mukenah shelves. All bathroom and ablution room cleaning activities are carried out with the standard of purity regulated in Islamic teachings.